Carprofen neither reduces postoperative facial expression scores in rabbits treated with buprenorphine nor alters long term bone formation after maxillary sinus grafting. (August 2016) - Hedenqvist, Patricia; Trbakovic, Amela; Thor, Andreas; Ley, Cecilia; Ekman, Stina; Jensen-Waern, Marianne
Abstract: In connection with bilateral maxillary sinus augmentation, the acute effects of the nonsteroidal anti-inflammatory drug carprofen on facial expressions and long-term effects on bone formation were evaluated in 18 male New Zealand White rabbits. A 10 × 10 mm bone window was drilled in the maxilla, the sinus membrane elevated and a titanium mini-implant inserted. One of two test materials was randomly inserted unilaterally and bovine bone chips (control) on the contralateral side in the created space. Rabbits were randomly allocated to receive buprenorphine plus carprofen (n = 9) or buprenorphine plus saline (n = 9) postoperatively. Buprenorphine was administered subcutaneously every 6 h for 3 days in a tapered dose (0.05–0.01 mg/kg) and carprofen (5 mg/kg) or saline administered subcutaneously 1 h before, and daily for 4 days postoperatively. To assess pain, clinical examination, body weight recording and scoring of facial expressions from photos taken before, and 6–13 h after surgery were performed. Twelve weeks after surgery the rabbits were euthanized and sections of maxillary bones and sinuses were analysed with histomorphometry and by qualitative histology. Carprofen had no effect on mean facial expression scores, which increased from 0.0 to 3.6 (carprofen) and 4.3 (saline), of a maximum of 8.0. Neither did carprofen have an effect on bone formation or implant incorporation, whereas the test materials had. In conclusion, treatment with 5 mg/kg carprofen once daily for 5 days did not reduce facial expression scores after maxillary sinus augmentation in buprenorphine treated rabbits and did not affect long term bone formation.